CORRECTIVE FEEDBACKS INTERACTION IN CLT-ADOPTED CLASSROOMS - Liskinasih, Ayu (Universitas Pendidikan Indonesia, 2016)
This case study aimed to examine corrective feedback (CF) pattern in the interactions of Indonesian EFL (English as Foreign Language) classrooms (a speaking and a grammar classrooms) which adopt CLT (Communicative Language Teaching). Two lecturers and twenty undergraduate English department students of an A-class university in Indonesia were involved as research participants. The findings revealed that the lecturers employed all types of CF to treat all types of errors. Explicit corrections were dominant in Speaking class as well as other explicit CF; whereas reformulations and prompt were equally distributed. Elicitation was dominant in Grammar class as well as other prompts; meanwhile, explicit and implicit CFs had similar proportion. The lecturers’ preferences were based on their beliefs on how their students learn foreign language and some factors such as the importance of CF to the instructional focus of the lesson, the possibility to generate student’s uptake, and also their empathetic values about students’ current language development. It was concluded that the provisions of CF in EFL classrooms reflect the application of CLT.